Transition Metal Complexes of Some Substituted Chalcones - Akuskar, S.K.; Chondhekar, T.K.; Dhuley, D.G. (Asian Journal of Chemistry, 2010)
The present paper reports the synthesis of a series of chalcones derived from 2-hydroxy/5´-chlorophenyl acetophenones and p-nitromethyl benzoic acid and benzaldehyde. The ligands synthesized were studied with regard to complex formation with V(II), Cr(II), Mn(II) and Fe(II).